2012
DOI: 10.1093/aob/mcs133
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of the Glycine max CYP707A gene family in response to drought and salt stresses

Abstract: The first biological evidence is provided that GmCYP7071a encodes an ABA 8'-hydroxylase through transgenic studies. Ten soybean GmCYP707A genes were identified, most of them expressed in multiple soybean tissues, and were induced by imbibition, dehydration and salinity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 54 publications
3
31
0
Order By: Relevance
“…The CYP707A gene family encodes ABA 8′- hydroxylases that control ABA catabolism, including four CYP707A genes in Arabidopsis (Saito et al, 2004 ), three in rice (Saika et al, 2007 ), two in peanut (Liu et al, 2014 ), three in bean (Yang and Zeevaart, 2006 ), three in potato (Suttle et al, 2012 ), five in maize (Vallabhaneni and Wurtzel, 2010 ), and 10 in soybean (Zheng et al, 2012 ). In our study, four genes were identified as candidate CYP707A genes in peach, among which PpCYP707A1 and PpCYP707A2 had been identified in a previous study (Leida et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The CYP707A gene family encodes ABA 8′- hydroxylases that control ABA catabolism, including four CYP707A genes in Arabidopsis (Saito et al, 2004 ), three in rice (Saika et al, 2007 ), two in peanut (Liu et al, 2014 ), three in bean (Yang and Zeevaart, 2006 ), three in potato (Suttle et al, 2012 ), five in maize (Vallabhaneni and Wurtzel, 2010 ), and 10 in soybean (Zheng et al, 2012 ). In our study, four genes were identified as candidate CYP707A genes in peach, among which PpCYP707A1 and PpCYP707A2 had been identified in a previous study (Leida et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…rapa includes three CYP707A3 genes, and two of them, Bra025083 and Bra021965 , exactly followed the pattern of membrane leakage ( Fig 7C ). The reported functions of CYP707A3, a major ABA 8’-hydroxylase, includes the dehydration response [ 79 , 80 ], stomata closure [ 81 ], and salt stress [ 80 ]. Our data suggests another function for this gene in HS conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The expressions of rice OsCYP707A5 in leaves [15] and all soybean GmCYP707A s in roots [18] were also increased sharply by high salinity. Salt stress involves both osmotic and ionic effects [24].…”
Section: Introductionmentioning
confidence: 94%